Multidisciplinary Management of Soft Tissue Sarcoma - Nystrom, Lukas M. (Hindawi Publishing Corporation, 2013)
Soft tissue sarcoma is a rare malignancy, with approximately 11,000 cases per year encountered in the United States. It is primarily encountered in adults but can affect patients of any age. There are many histologic subtypes and the malignancy can be low or high grade. Appropriate staging work up includes a physical exam, advanced imaging, and a carefully planned biopsy. This information is then used to guide the discussion of definitive treatment of the tumor which typically involves surgical resection with a negative margin in addition to neoadjuvant or adjuvant external beam radiation. Advances in imaging and radiation therapy have made limb salvage surgery the standard of care, with local control rates greater than 90% in most modern series. Currently, the role of chemotherapy is not well defined and this treatment is typically reserved for patients with metastatic or recurrent disease and for certain histologic subtypes. The goal of this paper is to review the current state of the art in multidisciplinary management of soft tissue sarcoma.